2010
DOI: 10.1007/s10709-010-9534-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of subterminal satellite (StSat) repeats in hominids

Abstract: Subterminal satellite (StSat) repeats, consisting of 32-bp-long AT-rich units (GATATTTCCATGTT(T/C)ATACAGATAGCGGTGTA), were first found in chimpanzee and gorilla (African great apes) as one of the major components of heterochromatic regions located proximal to telomeres of chromosomes. StSat repeats have not been found in orangutan (Asian great ape) or human. This patchy distribution among species suggested that the StSat repeats were present in the common ancestor of African great apes and subsequently lost in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…These subtelomeric caps are heterochromatic in nature and are completely absent from the karyotype of human and orangutan (Haaf and Schmid 1987;IJdo et al 1991;Ventura et al 2011). Subterminal heterochromatin has been thought to be composed primarily of a tandem array of a 32-bp subterminal satellite (StSat) creating large subterminal blocks of constitutive heterochromatic regions (Royle et al 1994;Koga et al 2011) adjacent to the canonical telomeric TTAGGG sequence (Greider and Blackburn 1989). While almost all gorilla chromosomes show the presence of subterminal caps, only half of chimpanzee chromosomes possess such structures (Fan et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These subtelomeric caps are heterochromatic in nature and are completely absent from the karyotype of human and orangutan (Haaf and Schmid 1987;IJdo et al 1991;Ventura et al 2011). Subterminal heterochromatin has been thought to be composed primarily of a tandem array of a 32-bp subterminal satellite (StSat) creating large subterminal blocks of constitutive heterochromatic regions (Royle et al 1994;Koga et al 2011) adjacent to the canonical telomeric TTAGGG sequence (Greider and Blackburn 1989). While almost all gorilla chromosomes show the presence of subterminal caps, only half of chimpanzee chromosomes possess such structures (Fan et al 2002).…”
mentioning
confidence: 99%
“…Unlike centromeric satellite sequences, which were well-characterized prior to the era of full genome sequencing (Rudd and Willard 2004), there are relatively few detailed molecular studies of the organization or evolution of the subterminal caps (Royle et al 1994). Conservatively, it has been estimated by dot-blot analysis that the subterminal heterochromatin constitutes >3 Mbp (0.1%) of the total genomic DNA of each species (Yunis and Prakash 1982;Koga et al 2011).…”
mentioning
confidence: 99%
“…Here, we assume that change from 0 to þþ always passes through þ . We assume, however, that a direct change from þþ to 0 can happen because such a change is likely to have occurred in the human lineage with the StSat repeats (Koga et al, 2011). One possible mechanism we have in mind is truncation of chromosomes and regeneration of the telomere.…”
Section: Telomere Region In An Apementioning
confidence: 99%
“…Fluorescent in-situ hybridization (FISH) analysis of an StSat repeat probe to metaphase chromosomes revealed that the repeats are present in the majority of chimpanzee and bonobo chromosomes and in all chromosomes of the gorilla (H Hirai, unpublished results). We have previously estimated the total size of the StSat repeats to be as large as 0.1% of the chimpanzee genome (Koga et al, 2011). The distribution of the StSat repeats among the hominid species (human and African great apes) is somewhat puzzling because humans are phylogenetically closer to chimpanzees and bonobos than to gorillas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation